The Digital Age and Its Transformations - Pertierra, Raul (Archīum Ateneo, 2020)
This paper explores the significance of digital technology in the contemporary world. After briefly discussing the effects of earlier technologies on everyday life, the paper assesses the consequences of interacting in a world where virtuality and simulacra often replace the real. Anthropology as a discipline is particularly effective in describing the changes experienced in a rapidly transforming social world.